Never standing still: Using evidence to improve visitors’ experiences at State Library of Queensland - Thorpe, Clare (Qualitative and Quantitative Methods in Libraries, 2017)
State Library of Queensland (SLQ) provides free access to information and services for all Queenslanders, as well as fulfilling the role of primary collector of Queensland’s document heritage. The Visitor Experience team leads the organisation in this goal, working to promote and nurture a positive and engaging experience for all visitors to State Library, regardless of whether people visit us in person, via our telephone service, website or social media channels. To do this, we gather, interpret and apply a range of quantitative and qualitative data sets, using evidence to inform decision making in service innovation. This case study will examine a selection of these data sources to demonstrate how SLQ responds to the evidence to create an agile, continuously improving service.  By investing in data collection and analysis, SLQ’s Visitor Experience team is able to respond in a timely and appropriate manner to the rapidly changing needs and expectations of our visitors.